(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Using specific historical examples, the author examines the causes and consequences associated with the problems of copyright protection in the Uzbek SSR, in particular the Uzbek branch of the All-Union Directorate for Copyright Protection. Based on an in-depth analysis of the problems of copyright protection in Uzbekistan in 1960-1970. a well-founded scientific conclusion has been made.